Exploring Students’ Academic Emotions Through a Conservation Education Program - Leni Sri Mulyani; Rifaatul Muthmainnah; Asep Rohayat; Wina Fitriyani (Postgraduate, University of Mataram, 2023)
Research and practice in educational settings should consider exploring the rich diversity of emotions experienced by students outside classroom settings, including nature clubs, as a conservation education program. This study aimed to conduct an exploratory case study to explore students' academic emotions during conservation education programs. The case study was carried out for four weeks to determine what can be learned from a single case about the students’ emotional aspects of the conservation education program in the Nature Club. Data collection is conducted through observation, interview, and collection of documents at the end of every activity. The data consisted of field notes and videotapes from observation, interview transcripts, and student emotions diary (SED). The research participant was 21 elementary students aged 9 to 11 who joined the Nature Club conducted by the Little Fire Pace (LFP) Community as one of their conservation education programs. The result shows that conservation content which is also part of science, can be learned and stimulate the emergence of students' academic emotions, both positive and negative. The dominant emotion in nature club activities is the happy emotion, and the slightest emotion arising from this activity is disgust. Then the results of student interest in all activities were more remarkable than boredom. Finally, suggestions are made on implications for teacher or pre-service teacher education for conservation or science education.